ANALISIS PENGGUNAAN KODE BAHASA DALAM KOMUNIKASI RUANG LINGKUP MAHASISWA FIP UMJ - Achmad Fauzan; Ratna Dewi Kartikasari (Universitas Madura, 2021)
The large variety of languages used by FIP UMJ students are bilingual and multilingual. This led to the selection of codes used in the utterances of UMJ FIP students. The purpose of this study was to describe the selection of codes used by UMJ FIP students. Based on the Betawi students' speech, the code selection was (1) single language, which includes non-formal Indonesian, Betawi language, and Sundanese language; (2) code switching; and (3) code mix.